Application study of infrared free-electron lasers towards the development of amyloidosis therapy - Mikiko Jindo; Kazuhiro Nakamura; Hisashi Okumura; Koichi Tsukiyama; Takayasu Kawasaki (Journal of Synchrotron Radiation, 2022)
Amyloidosis is known to be caused by the deposition of amyloid fibrils into various biological tissues; effective treatments for the disease are little established today. An infrared free-electron laser (IR-FEL) is an accelerator-based picosecond-pulse laser having tunable infrared wavelengths. In the current study, the irradiation effect of an IR-FEL was tested on an 11-residue peptide (NFLNCYVSGFH) fibril from β2-microglobulin (β2M) with the aim of applying IR-FELs to amyloidosis therapy. Infrared microspectroscopy (IRM) and scanning electron microscopy showed that a fibril of β2M peptide was clearly dissociated by IR-FEL at 6.1 µm (amide I) accompanied by a decrease of the β-sheet and an increase of the α-helix. No dissociative process was recognized at 6.5 µm (amide II) as well as at 5.0 µm (non-specific wavelength). Equilibrium molecular dynamics simulations indicated that the α-helix can exist stably and the probability of forming interchain hydrogen bonds associated with the internal asparagine residue (N4) is notably reduced compared with other amino acids after the β-sheet is dissociated by amide I specific irradiation. This result implies that N4 plays a key role for recombination of hydrogen bonds in the dissociation of the β2M fibril. In addition, the β-sheet was disrupted at temperatures higher than 340 K while the α-helix did not appear even though the fibril was heated up to 363 K as revealed by IRM. The current study gives solid evidence for the laser-mediated conversion from β-sheet to α-helix in amyloid fibrils at the molecular level.